A Comparative Assessment of School Psychological Services in a Select Higher Education Institution - Dizon, Alvin Ryan Alcantara (UI Scholars Hub, 2026)
This quantitative descriptive-comparative research assessed the effectiveness and adequacy of SPS in a higher education institution in Southern Tagalog, Philippines. This study aimed to identify the perceived importance of both direct and indirect psychological services and evaluate the extent of administrative support in implementing them. Participants included 75 administrative personnel, 30 mental health staff, and 384 faculty and student respondents selected through stratified proportional sampling. Data were collected using a validated and reliable instrument (Cronbach’s alpha = 0.966-0.989) and analyzed using analysis of variance and independent sample t-tests. Results revealed that all respondent groups rated direct services as very important (M = 4.17-4.48) and indirect services as moderately important (M = 3.91-4.37). Administrative support was moderately high (M = 3.28-4.25). Strengthening collaboration, policy support, and infrastructure development can enhance service delivery and improve academic and psychological well-being.